A Descriptive Study of Principal’s Strategy in Managing BOS Funds to Support School Digitalization and Infrastructure Improvement toward Education 4.0 - Roihatul Jannah; Suroso Suroso; Sutrisno Sutrisno (FKIP - Universitas Riau, 2026)
The rapid development of digital technology in the Education 4.0 era requires schools to optimize financial resources, particularly School Operational Assistance (BOS) funds, to support digitalization and infrastructure improvement. This study aims to analyze the principal's strategy in managing BOS funds to enhance school digitalization and infrastructure development in a public junior high school in Central Java, Indonesia. This research employed a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document analysis involving the principal, teachers, and administrative staff, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The results reveal that the principal implements systematic planning through the School Activity and Budget Plan (RKAS), prioritizes digital facility development such as internet access and learning devices, and conducts regular evaluation to ensure accountability and efficiency. Leadership capacity, stakeholder collaboration, and effective resource management are identified as key factors influencing successful BOS fund utilization. In conclusion, strategic and well-managed BOS fund allocation significantly contributes to improving digital learning and strengthening school infrastructure toward Education 4.0.